Silicon Effects Depend upon Insect Herbivore Guild and Has Limited Influence on Gall-Inducing Insects of Bauhinia brevipes - Guilherme Ramos Demetrio; Henrique Venâncio; Janaina Correa Batista; Jean Carlos Santos (Plants)
Silicon (Si) is a widely recognized element in plant defense, often enhancing resistance to herbivory by strengthening cell walls and deterring feeding by external herbivores. However, its impact on internal, endophytic herbivores, such as gall-inducing insects, remains underexplored. This study investigates the role of silicon in Bauhinia brevipes, focusing on its effects on herbivory by insects. We hypothesize that while silicon strengthens plant tissues and reduces feeding by external herbivores, it may have a limited effect on internal feeders, such as gall-inducing insects. Our results indicate that silicon accumulation in leaves significantly reduces herbivory by chewing insects but has no direct effect on the occurrence of gall-inducing insects. Silicon content in galled tissues was lower compared to healthy leaves, suggesting that gall-inducing insects may manipulate silicon distribution to mitigate its defensive effects. Our results indicate that hypersensitivity reactions were positively influenced by silicon, highlighting the role of this element in enhancing localized defense mechanisms. Our findings reveal silicon’s tissue-specific roles in plant defense, emphasizing the need for more research on its nuanced interactions with endophytic herbivores and implications for ecological applications. This research contributes to the literature on silicon’s multifaceted role in plant–herbivore interactions and its potential applications in sustainable pest management.